2016
DOI: 10.1037/pst0000058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-focused psychotherapies for eating disorders come of age.

Abstract: This is a commentary on 3 case studies of relationship-focused therapies for eating disorders. The 3 approaches vary along a number of dimensions, but nevertheless share important similarities especially related to the role played by variables such as interpersonal problems and affect dysregulation. I briefly review research on interpersonal- and attachment-based models of eating disorders that provide the evidence-base for theories of therapy that are relationship-focused. The Interpersonal Psychotherapy case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
3
0
5
Order By: Relevance
“…Similar to other developing conceptualizations of therapeutic change mechanisms that focus on the role of early relational patterns in adult emotional regulation and dysregulated eating (41,42), I posit that patients with dysregulated eating may benefit from psychotherapeutic approaches that address the underlying regulatory issues that are preverbally embedded in somatic experience and in the implicit relational world of attachment misattunements to facilitate the repair of the developmentally impaired capacity of self-regulatory functioning. The therapeutic aim involves helping patients to regulate impulses, fill the deep emotional void, and move away from the primal call of food to enable the development of more adaptive self-regulatory mechanisms, specifically more self-soothing processes, greater self-efficacy, a more integrated sense of self, enhanced tolerance for intimacy, and a healthier authentic relatedness.…”
Section: Attachment-based Psychotherapymentioning
confidence: 95%
“…Similar to other developing conceptualizations of therapeutic change mechanisms that focus on the role of early relational patterns in adult emotional regulation and dysregulated eating (41,42), I posit that patients with dysregulated eating may benefit from psychotherapeutic approaches that address the underlying regulatory issues that are preverbally embedded in somatic experience and in the implicit relational world of attachment misattunements to facilitate the repair of the developmentally impaired capacity of self-regulatory functioning. The therapeutic aim involves helping patients to regulate impulses, fill the deep emotional void, and move away from the primal call of food to enable the development of more adaptive self-regulatory mechanisms, specifically more self-soothing processes, greater self-efficacy, a more integrated sense of self, enhanced tolerance for intimacy, and a healthier authentic relatedness.…”
Section: Attachment-based Psychotherapymentioning
confidence: 95%
“…Several psychotherapeutic method involves the above written attachment-related factors, such as the emotion-focused family therapy ( Robinson Dolhanty, & Greeberg, 2015), and dialectical behavior therapy (Rizvi, Steffel, & Carson-Wong, 2013). Although psychodynamic approaches also contain various attachment-related aspects of psychotherapies such as paternal relationships, transference or emotion-regulation (Tasca, 2016;Thompson-Brenner, 2014), the efficacy of interventions focusing exclusively on patients' attachment-functioning were only recently tested (Illing et al, 2010;Maxwell, Tasca, Ritchie, Balfour, & Bissada, 2014;Tasca et al, 2006). Related efficacy studies showed that the more the patient's attachment functioning improved during the course of the treatment, the better outcomes could be observed (Illing et al, 2010;Maxwell et al, 2014;Tasca et al, 2011Tasca et al, , 2013.…”
Section: The Efficacy Of Attachment-interventions In the Treatment Of...mentioning
confidence: 99%
“…However, when these attachment-related factors contribute to the maintenance of eating disorder symptoms, they can serve as intervention points in the course of personalized treatments. This implies the usefulness of longer, relationship-focused psychotherapies in eating disorders (Tasca, 2016).…”
Section: The Summary Of Therapeutically Relevantmentioning
confidence: 99%
“…As mudanças mais notáveis foram sua maior habilidade no funcionamento reflexivo e uma maior coerência em sua narrativa que lhe permitiu ser mais estável emocionalmente, diminuindo os sintomas alimentares. A descrição deste caso é um importante lembrete de que no transtorno alimentar os sintomas não podem ser tratados ignorando a disfunção interpessoal e a incoerência na narrativa do apego (Tasca, 2016).…”
Section: Revisão Integrativa: Coleta De Dados E Análise Críticaunclassified
“…Segundo o autor, teoria e pesquisa sobre fatores interpessoais e regulação emocional que determinam os sintomas de transtorno alimentar percorreram um longo caminho nas últimas décadas. As terapias para tratar transtornos alimentares que se baseiam nesta pesquisa, nos domínios interpessoal e de apego, estão amadurecendo e fornecem aos terapeutas uma gama mais ampla de opções terapêuticas que podem ser verdadeiramente personalizadas para seus pacientes (Tasca, 2016).…”
Section: Subcategoriaunclassified